Kidney Disease in Oman: a View of the Current and Future Landscapes (Iranian Journal of Kidney Diseases, 2017)
Oman is located in the southeast of Arabian Peninsula with a relatively young population of about 3 831 553 people. The Ministry of Health, which is the healthcare provider, is facing a challenge with the increased levels of noncommunicable diseases including chronic kidney disease. A growing number of patients progress to end-stage kidney disease (ESKD), demanding renal replacement therapy. In 2014, there were 1339 of ESKD patients receiving dialysis and almost 1400 patients received kidney transplants. The estimated annual incidence of ESKD is 120 patients per million population. Diabetes mellitus and hypertensive nephropathy are the commonly identified causes of ESKD. Many patients with glomerulonephritis, systemic lupus erythematosus, nephrolithiasis, and inherited kidney disease present with advanced chronic kidney disease. This article reviews the current status of kidney disease in Oman and addresses the present and future needs, through a systematic-review of all related papers.